Abuse in world religions: articulating the problem - Stiebert, Johanna (Rape culture, religion and the Bible, 2025)
Introduction 1. Judaism, Our Revolt-ing Women: Bringing Women Together 2. Hinduism, From God's Slaves to Sex Slaves: The Plight of Devadasis in Hinduism 3. Christianity, Violence and Abuse in Christian Contexts: The Example of Domestic Abuse 4. Islam, Developments in the field of understanding Spiritual Abuse within Muslim Contexts 5. Sikhi(sm), What's faith got to do with it? Domestic Violence and Abuse in Sikh Communities